Case Report: Two cases of chemotherapy refractory aggressive variant prostate cancer with extreme durable response to PARP inhibitor - Jiang, Bohao; Bi, Yifan; Chen, Yiming; Bi, Jianbin; Deng, Jian; Zhang, Gejun (Frontiers in Oncology, 2025)
BackgroundAggressive variant prostate cancer (AVPC) represents a distinct clinical subset characterized by resistance to novel hormone therapies and an unfavorable prognosis, frequently associated with the concurrent loss of tumor suppressor genes (TSG) such as PTEN, RB1, and TP53. While the progression-free survival (PFS) and overall survival (OS) of AVPC are relatively short, the optimal first-line treatment remains unclear.PresentationIn this case report, we presented two de novo AVPC cases who have ultimately benefited from the usage of PARP inhibitors. The first patient was a 64-year-old male who was diagnosed during prostate biopsy featured by mutations in PTEN, and loss of RB1, BRCA2, ATM, and FANCA. He was treated with docetaxel/albumin-bound paclitaxel and cisplatin in the first line. Second-line therapy was applied with radiotherapy and Olaparib after failure of first-line therapy, resulting in a PSA response sustained for three years. The second case was a 75-year-old male with localized neuroendocrine feature and mutations in TP53, loss of RB1 and HDAC2. He was treated with sustained ADT and chemotherapy in the first-line treatment. Radiotherapy and Fluzoparib + abiraterone was applied as subsequent treatments with a PSA response for 2 years.ConclusionsThese two cases demonstrating a satisfactorily durable response to PARP inhibitors indicating its clinical benefit in AVPC population with detected DNA damage response (DDR) defects. The survival improvement with PARP inhibitors observed in our clinical experiences, along with current advances in tumor sequencing provide more information on future clinical trials and explorations of innovative therapies in AVPC population.